Androgen receptor, oxidative stress and inflammation at the crossroads of skin diseases - Yiumo Michael Chan; Yen-ting Liu; Hardy W Chan (International Journal of Dermatology and Clinical Research - Peertechz Publications, 2022)
Skin is the largest organ of the human body and acts as a protective barrier as our first line of defense. The development of effective treatments for skin diseases represents one of the biggest challenges in drug discovery. The pathogenesis of many skin disorders is complex and multifactorial.